Phosphorylated human tau associates with mouse prion protein amyloid in scrapie-infected mice but does not increase progression of clinical disease. Issue 4 (3rd July 2016) - Race, Brent; Phillips, Katie; Kraus, Allison; Chesebro, Bruce
ABSTRACT: Tauopathies are a family of neurodegenerative diseases in which fibrils of human hyperphosphorylated tau (P-tau) are believed to cause neuropathology. In Alzheimer disease, P-tau associates with A-beta amyloid and contributes to disease pathogenesis. In familial human prion diseases and variant CJD, P-tau often co-associates with prion protein amyloid, and might also accelerate disease progression. To test this latter possibility, here we compared progression of amyloid prion disease in vivo after scrapie infection of mice with and without expression of human tau. The mice used expressed both anchorless prion protein (PrP) and membrane-anchored PrP, that generate disease associated amyloid and non-amyloid PrP (PrPSc) after scrapie infection. Human P-tau induced by scrapie infection was only rarely associated with non-amyloid PrPSc, but abundant human P-tau was detected at extracellular, perivascular and axonal deposits associated with amyloid PrPSc. This pathology was quite similar to that seen in familial prion diseases. However, association of human and mouse P-tau with amyloid PrPSc did not diminish survival time following prion infection in these mice. By analogy, human P-tau may not affect prion disease progression in humans. Alternatively, these results might be due to other factors, including rapidity of disease, blocking effects by mouse tau, or low toxicity of human P-tau in this model.